PERTANGGUNGJAWABAN KORPORASI OLEH DIREKSI TERHADAP TINDAK PIDANA KORUPSI (STUDI KASUS PUTUSAN NOMOR 003/PIDANA. KHUSUS-TINDAK PIDANA KORUPSI/2018. PT.DKI) - Rani Asmara; Dian Adriawan DG Tawang (Jurnal Hukum Adigama, 2020)
Criminal liability by the Board of Directors stipulated in article 2 paragraph (1) of law number 31 of 1999 Jo Law No. 20 of 2001 on the Eradication of corruption crimes against the case of corruption crimes contained in the ruling of a court number 003/Pid. Sus-TPK/2018/PT. DKI to maintain the intermediary of the officers because the legal entity is always realized through human deeds, so that the delegation of criminal liability contained in humans with this is represented by directors in accordance with the provisions of article 1 number 4 Law No. 40 2007 year about limited liability company. Therefore, the problems that need to be studied further, namely as follows: How is the corporate responsibility of the directors of corruption against criminal acts? To examine the problem, the author uses normative research methods. The results of the study indicated that the Board of Directors may have requested a criminal liability dispute in accordance with the provisions of article 2 paragraph (1) article 18 paragraph (1) and (2)  31 of 1999 Jo Act No. 20 of 2001 on the Eradication of criminal corruption. The author concluded that the criminal liability against corruption crimes was carried out by the Board of directors or the administration, because in the case of corporations can only be penalized by criminal sanctions relating to compensations, because the corporation is a legal entity that cannot be held to be criminal liability in the form of prison confinement and has no outward body form.